Qualidade de vida de idosos no contexto do trabalho e suas Representações Sociais - Costa, Iluska Pinto da (2015)
Introduction: Population aging brings with it the active presence of the elderly in the labor market, making it a challenge to provide a better quality of life (QOL) for this group. Thus, the present study aims to evaluate the QOL of working and not working elderly people; and to know their social representations on QOL. Method: An exploratory and descriptive study with 113 elderly of a social group in the city of Cajazeiras - PB. Data collection was carried out through interviews, using a sociodemographic questionnaire, the Free Association Test (FAT) and WHOQOL-BREF and WHOQOL-OLD. Sociodemographic data and the quality of life verification tests were processed using the SPSS version 2.0 and FAT by Iramuteq software version 0.6. Results: 44.2% of the 113 elderly work and 55.8% do not. In both groups the majority were women and 87.3% of those women do not work. In the group of older people working, 32% of seniors belong to the age group of 60-64 years old and 28.6% of the group that does not work are between 65-69 years old. The civil status married predominates in the working group (56%) and incomplete primary school education in both groups, with 48.0% of those who work and 61.8% of those not working. Regarding family income, 48.0% of seniors who work and 65.1% of those who do not work earn between one and three times the minimum wage. Among retirees, 72.0% remain working while 90.5% do not. Regarding the family arrangement, it was identified that 23.8% of the elderly who do not work live only with their spouse, and 30% of those working live with spouse and child. As for religion, 80.0% of those who work and 92.1% of those who do not work are Catholics. On the assessment of QoL, the elderly working had higher average scores in most areas of the WHOQOL-BREF and facets of WHOQOL-OLD, demonstrating the psychological domain (70.08) and Sensory Skills facet (72.50). Among the elderly who do not work the scores for QoL were detected in psychological domain (66.79) and facet Death and Dying (72.2). Considering the social representations about QoL built by the elderly, four classes emerged from textual analysis: Social Aspects, Economic Conditions, Positive Feelings and Participation in the group. About the relationship between work and QOL, it was detected significant differences among the representations of QOL in both groups: older people working, associate QOL to material goods, while those who do not work, see the quality of life associated with emotional issues, positive feelings and social interactions developed from living in groups. Conclusion: It was observed among older people working, higher scores in the fields and facets of instruments that analyze QOL, demonstrating that the work allows the elderly to maintain their physical, mental and sensory skills and social relationships. It was also felt that the social representations attributed to quality of life demonstrated its relationship to the variable job.